RADIATIVE PROTON CAPTURE ON 3H AT ASTROPHYSICAL ENERGIES AND ITS ROLE IN THE INITIAL STAGE OF STAR FORMATION - A.V. Dzhazairov-Kakhramanov; L.T. Karipbayeva (Academic Scientific Journal of Computer Science, 2019)
Calculations of the astrophysical S-factor of the proton radiative capture on 3H at energies from 1 keV to 10 MeV in the frame of the Modified Potential Cluster Model (MPCM) with classification of orbital states of nuclear particles according to Young tableaux and isospin were carried out. The explanation of the used phenomenological model MPCM was done. The classification of the p3H states according to Young tableaux was given. The p3H interaction potentials and phase shifts of the p3H elastic scattering were found.